Flue Gas Desulphurization using Adsorbent Prepared from Waster Abundant Eggshell - Phang, Yee Jian (2015)
Flue gas desulphurization has been sky rocketing in recent years due to the rapid developing industry that release sulphur dioxide gas. Conventional use of commercialise calcium oxide derived from calcium carbonate has been the best adsorbent used in Flue gas desulphurization but not unsustainable. Therefore, eggshell waste has been introduced to reduce the consumption of commercial calcium oxide to prevent depletion of natural resource so that we can perform flue gas desulphurization and achieve the required standards. Using hydration method with heating mantle can greatly improve the adsorption capacity of eggshell waste by prioritizing a few parameters such as hydration temperature and hydration time. By using gas analyser to determine the gas adsorption capacity, the highest adsorption capacity of eggshell sample are achieved at 3.936 gso2/geggshell hydrated at 90°C and 30 hour hydration time, compare to highest adsorption capacity of commercial calcium oxide at 15.521 gso2/gcao hydrated at 80°C and 1 hour hydration time.